(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2016)
Background. Pain after breast cancer surgery leads to long term disability. Music therapy is non-invasive, inexpensive supplementary therapy way, which helps to improve emotional and psychological condition, to reduce stress, anxiety and pain. Nevertheless, there is a lot of knowledge about the benefts of music therapy, and it is a lack of scientifc research, which could advocate for music therapy beneft after breast cancer surgery. Research aim. To evaluate music therapy effect on women pain after breast cancer surgery. Research tasks. To assess the pain of women using a visual analogue scale (VAS) before and after the application of music therapy in the study and control groups. Methods. An analysis of scientifc / medical literature was made. Quantitative research method was selected. Criteria for involvement into scientifc research were women after breast cancer surgery. In research group music therapy was applied. It consisted of 25 patients with an average age of 52.23 ± 9, 04 years. A control group consisted of 25 patients with an average age of 56.17 ± 7.84 years. Music therapy was not applied in control group. The research instrument was the VAS. The data were collected before the application of music therapy and after. Music therapy sessions were used after breast cancer surgery the whole period of rehabilitation. Sessions were held in a recreation room 6 times a week, session duration of 30 – minute. The Baroque and the New Age music were used in music therapy sessions. Listening to music, women were asked to close their eyes, relax and breathe deeply. To ensure the most accurate results of the study participants were asked to avoid listening additional music. Results. Before using music therapy the difference of pain intensity data (measured by VAS) was not statistically signifcant in the research and control groups. After music therapy the study group showed a statistically signifcant decrease in pain intensity: before music therapy pain intensity score of 6.54 ± 1.45, after music therapy – 3 ± 0.98 points (p < 0.001); control group pain intensity also decreased: before music therapy 5.58 ± 1.56 points, after music therapy 2.88 ± 1.91 points. Conclusion. After breast cancer surgery, and after the completed rehabilitation, pain decreased in the research group, where music therapy was applied (p < 0.001); in the control group, where music therapy was not applied, pain also decreased. (p < 0.05). Difference between the change of pain in study group and in control group was not statistically signifcant. Pain change in the study group was not signifcantly higher than the control group. Keywords: music therapy, pain, breast cancer.